Mesothelial-mesenchymal transitions in embryogenesis. - Carmona-Mejías, Rita María; Ariza Medina, Laura Maria; Cano, Elena; Jiménez-Navarro, Manuel Francisco; Muñoz-Chápuli-Oriol, Ramón (Elsevier, 2018)
Most animals develop coelomic cavities lined by an epithelial cell layer called the mesothelium. Embryonic mesothelial cells have the ability to transform into mesenchymal cells which populate many developing organs contributing to their connective and vascular tissues, and also to organ-specific cell types. Furthermore, embryonic mesothelium and mesothelial-derived cells produce essential signals for visceral morphogenesis. We review the most relevant literature about the mechanisms regulating the embryonic mesothelial-mesenchymal transition, the developmental fate of the mesothelial-derived cells and other functions of the embryonic mesothelium, such as its contribution to the establishment of left-right visceral asymmetries or its role in limb morphogenesis.
https://openpolicyfinder.jisc.ac.uk/id/publication/11412
Keywords: Morfogénesis; Embriología; Mesothelium; Organogenesis; Coelomic epithelium